Optimizing post-operative opiate prescribing following gynecologic surgery - Katherine M. Croft; Bethany M. Sarosiek; Elisa Trowbridge; C. Page Muthusubramanian; Traci Hedrick; Susan C. Modesitt (Elsevier, 2022)
Background: Post-operative opiate prescribing has traditionally been stratified by procedure type with little regard for patient opiate utilization. We sought to evaluate peri-operative factors associated with patient opiate utilization post-operatively to develop, implement, and assess a discharge prescribing intervention. Study design: This was a quality improvement study of opiate prescribing practices for patients undergoing gynecologic surgery on an enhanced recovery pathway (ERAS) pre- and post-discharge prescription intervention. In the pre-intervention cohort (12/2018 to 05/2019), peri-operative factors (demographic, procedure, and pain scores) associated with post-operative patient opiate usage and quantity of opiate prescribed were identified. A discharge planning intervention based solely on opiate usage was implemented. The pre- and post-intervention cohort (07/2020 to 09/2020) were compared to assess changes in post-operative opiate prescribing and refill requests. Results: There were 220 patients in the pre-intervention cohort and 120 patients post-intervention. Post-operative opiate usage in the pre-intervention cohort was correlated only with pain score and age (p < 0.001, p = 0.04). Quantity of opiate prescribed was correlated only with procedure type and not reflective of patient opiate usage. Using this information, a discharge planning intervention for opiate prescription informed by opiate usage in the twenty-four hours prior to discharge was added to the discharge order set. Post-intervention, adherence to recommended prescription was 40.8%. Opiate prescriptions decreased from a mean 27.3 tablets to 14.8 tablets (p < 0.001). Conclusions: A tailored, patient specific approach to post-operative opiate prescribing can significantly decrease the quantity of opiates prescribed.